(untitled) (Journal of Bio-Science, 2023)
The present study was conducted to assess the features of the stinging catfish Heteropneustes fossilis (Bloch) in terms of total length (TL), total weight (TW) and growth performance and survival rate after treatment of fish feed with a synthetic male hormone, 17 α-methyltestosterone (17 α-MT) under laboratory conditions. Results showed that TL in the untreated (C) and T1 group of fishes differed significantly (p<0.05) even though the overall effect of the hormone did not influence TL of the fishes under study (p = 0.085). A similar result was observed for TW, but the overall impact of 17-αMT on TW of H. fossilis was highly significant one (p<0.001), indicating that the TW was increased much more than the TL due to the hormone treatment in the experimental fishes. Growth performances of the fishes in terms of their gains in TL and TW due to the hormone treatment and over a rearing period of four months from March to June showed that compared to the control groups, all three treatment groups increased in both the morphometric parameters in H. fossilis. The increases in TW were more drastic than the corresponding increases in TL. Notably, the hormone treatments did not affect the survival of the experiment fishes under study. Histopathological changes in the intestine of T2 fishes were characterized by hemorrhage and degeneration of villi, whereas hemorrhage, degeneration of serosa and rapture of villi were remarkable in T3 group. Enlarged glomeruli, lots of vacuoles, disorganization of renal tubules and necrosis were observed in T2 whereas the T3 group was characterized by vacuoles, disorganization of tubules, enlarging glomeruli and wider tubular lumen. Since the present results clearly demonstrated that 17 α-MT treatments enhanced the total length and weight as well as growth performance of H. fossilis, carefully designed experiments with appropriate doses of the hormone in fish feed would be beneficial for the commercial production and conservation of this popular catfish in the country. J Bio-Sci. 30(1): 131-141, 2022 (June)